1464 Breaking Tradition – A Rural DGH's Experience of The Management of Acute Appendicitis During the First Wave of the COVID-19 Pandemic. (12th October 2021) - Zahari, F; Byrne, H; Roslan, F; Ali, M; Mitrofanova, O; Da Silva Bento, E; Rao, M
Abstract: Aim: Acute appendicitis (AA) is the most common abdominal surgical emergency in the UK and traditionally, operative management is the mainstay of treatment. However, during the first wave of the COVID-19 pandemic, ACPGBI discouraged laparoscopy, due to potential risks of aerosol viral transmission. We aimed to review clinical outcomes of patients treated for AA at our DGH prior to and after the change in ACPGBI guidance. Method: The first 30 patients treated for AA prior to (Group A) and following the update in ACPGBI guidance (Group B), were identified. Results: Group A : 7% managed conservatively vs 93% operative management. Group B : 74% managed conservatively vs 26% operative management. No statistically significant difference was seen in the rate of post-operative complications, or readmission. In Group B, of those managed conservatively and then readmitted, 75% underwent an operation (RR < 1.00). The average length of stay (LOS) of those managed conservatively in Group A was 3.5 days vs 2.4 days in Group B (p < 0.05). Statistically significant differences in LOS were also observed in patients who underwent surgery - Group A 5.5 day vs 8.25 days in Group B (p < 0.001). Conclusions: In conclusion, the change in ACPGBI guidance in the early stages of the COVID-19 pandemic, saw statistically significant differences in LOS at our DGH. A shorter LOS in those conservatively managed in Group B could be explained by hospital bed pressures. An increase in LOS for Group B patients with operative management is understandable, as only cases of complicated AA, or those readmitted underwent emergency surgery.